Bio-oil anaerobic fermentation as a starting point for the production of PHA by mixed cultures - Paulo, Inês Filipa Cópio (2018)
Nowadays, the replacement of petroleum products by renewable carbon is one of the great concerns in the World. Under this strategy the production of polyhydroxyalkanoates (PHA) starting from a low-cost residue shows with high potential for applications. Combining this with a mixed microbial culture (MMC) with polymer accumulation capacity allows the necessary conditions for the production of PHA at low cost. The main objective of this study was to provide a different valorisation scheme for wood residues considering a new process to be integrated into a global biorefinery approach. Pinewood bio-oil was used as the carbon substrate for the production of PHA in a three-step process: pre-fermentation, culture selection and PHA production, all systems being operated with MMC. In the acidogenic fermentation, several conditions were tested, from which the medium containing 8 g/L of sugars with a C: N: P ratio of 100:3:1 and 10 days of retention time stand out, reaching a maximum short-chain organic acid (SCOA) concentration of 6.3 g/L and an acidification degree of 0.14 gCOD/gCOD. The culture selection reactor operated under aerobic conditions was fed directly with pure bio-oil, reaching a maximum PHA content of 13.93%. Finally, after the adaptation of the culture, accumulation tests were performed in which the maximum PHA content was 35.60%, using fermented bio-oil as a substrate. It was concluded that the pinewood bio-oil is a possible substrate for PHA production.